Every Time I Feel the Spirit Religious Experience and Ritual in an African American Church - Nelson, Timothy (Qualitative Studies in Religion, 2004)
Dreams and visions, prophetic words from God about "dusty souls," speaking in tongues while "in the spirit"-narratives of these and similar events comprise the heart of Every Time I Feel the Spirit. This in-depth study of a Black congregation in Charleston, South Carolina provides a window into the tremendously important yet still largely overlooked world of African American religion as the faith is lived by ordinary believers. For decades, scholars have been preoccupied with the relation between Black Christianity, civil rights, and social activism. Every Time I Feel the Spirit is about black religion as religion. It focuses on the everyday experience of religion in the church, congregants' relationships with God, and the role that God and Satan play in congregants' lives-not only as objects of belief but as actual agents. It explores the concepts of religious experience and religious ritual, while emphasizing the attributions that people make to the operation of spiritual forces and beings in their lives. Through interviews and field work, Nelson uncovers what religious people themselves see as important about their faith while extending and refining sociological understandings of religious ritual and religious experience